A note on maintenance of ethnic origin diet and healthy eating in understanding society - Ayse K. Uskul; Lucinda Platt (University of Essex, Institute for Social and Economic Research (ISER), 2014)
In this note we take a first look at the extent to which ethnic minorities in the UK maintain or diverge from the diet associated with their country of origin; and whether those who maintain their ethnic origin diet eat more or less healthily. We find that immigrants are more likely to eat food of ethnic origins than minority group members born in the UK. Those of Indian, Pakistani and Bangladeshi ethnicity are more likely than other minority groups to eat food of ethnic origin whether immigrant or UK-born. UK born minorities who eat ethnic origin food less often also eat fruits and vegetables less often. Thus maintenance of an ethnic origin diet appears to be associated with healthier eating patterns.
Keywords: J15; I18; Z13; 330; ethnicity; diet; healthy eating